If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b = 9b + -24 Reorder the terms: b = -24 + 9b Solving b = -24 + 9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9b' to each side of the equation. b + -9b = -24 + 9b + -9b Combine like terms: b + -9b = -8b -8b = -24 + 9b + -9b Combine like terms: 9b + -9b = 0 -8b = -24 + 0 -8b = -24 Divide each side by '-8'. b = 3 Simplifying b = 3
| 9y^2-33y+24= | | -9+2(4g-7)=9 | | x+4=9-2x | | m+4+5=22 | | 33=x+4 | | z=1+i^12 | | 14+4=x+5x | | -160+-52x+1x^2+x^3=0 | | 5x(3x+5)=0 | | k^3-18k-7k^2=0 | | (3s+20)(s+1)=-22 | | (3s+20)(s+1)=-20 | | 4x-8=5x-2 | | 9x+3=8x+19 | | p(p+1)=6 | | 2m^2-12m=2m-24 | | x^3-13x^2+36x=0 | | x+6=2x-8 | | 3x-5=x+3 | | 5m(5m+4)=-4 | | 2x^2-9x=26 | | 2x+6=19-3 | | 4x^2-21x=-5 | | 8x^2=-9x | | p^2=22p | | 2(2x+3)=4x-6 | | 5x+2=x+17 | | 10y-2=7+3y | | 8.4+x=-3.9 | | x-(-9)=-9 | | 49y^2-1=0 | | 32xl=288 |